Poor Institutions, Rich Mines: Resource Curse and the Origins of the Sicilian Mafia - Paolo Buonanno; Ruben Durante; Giovanni Prarolo; Paolo Vanin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
This study explains the emergence of the Sicilian mafia in the XIX century as the product of the interaction between natural resource abundance and weak institutions. We advance the hypothesis that the mafia emerged after the collapse of the Bourbon Kingdom in a context characterized by a severe lack of state property-right enforcement in response to the rising demand for the protection of sulfur - Sicily's most valuable export commodity - whose demand in the international markets was soaring at the time. We test this hypothesis combining data on the early presence of the mafia and on the distribution of sulfur reserves across Sicilian municipalities and find evidence of a positive and significant effect of sulphur availability on mafia's diffusion. These results remain unchanged when including department fixed-effects and various geographical and historical controls, when controlling for spatial correlation, and when comparing pairs of neighboring municipalities with and without sulfur.
Keywords: K42; N33; N54; O13; O43; 330